ANALISIS USAHA DAN PERMINTAAN PEMBIBITAN LAI (Durio kutejensis) DI DESA BATUAH KECAMATAN LOA JANAN KABUPATEN KUTAI KARTANEGARA - Damayanti, Arista; Handayani, Pinto Rukmi (Agriculture Faculty, University of Kutai Kartanegara, Indonesia, 2018)
Lai is one of the duriogenealogy who have the potential of domestic and export markets are high enough to accompany the durian. Lai fruit is one of the tropical fruits that are now popular as a source of nutritious food and exotic fruit typical of Kutai Kartanegara. To be able to produce quality fruit crops of quality seeds are required of superior varieties and also professionally managed agribusiness farming. Because basically the concept of superior seed is a seed that comes from a merger between the rootstock and entris so as to form a new plant that is compact and has the advantage.This research was conducted in Batuah Village, in Loa Janan, that is Lai nursery business. This study aims to knowBreak Even Point (BEP), R/C ratio and demand function.The results of this study from the calculation of Break Even Point all respondents known that Lai nursery in Batuah Village in a state of profit because it has exceeded the point of breakeven. And the calculation of R / C Ratio at the nursery business in Batuah Village get the highest number that is 6,78 and the lowest 1,67.This indicates that the nursery business is profitable.The demand function is Y = 4263,84 -0,140X1 + 0,062 X2.The result showed that increasing price Lai seeds will be decreasing demand and increasing price Durian seeds will be increasing demand of Lai seeds. Keywords: Nursery, Lai, BEP,Demand